Stress-induced production of lipids in oleaginous microalgae for biofuel optimization - Teichner,Eric M (PeerJ PrePrints, 2015)
Emerging concerns over energy security and accelerating climate change have led to a global interest in developing a sustainable biofuel. Recently, it was determined that algal biofuels can be possibly cultured in a wastewater medium due to high levels of nutrients nitrogen, phosphorus, and potassium (NPK), reducing economic costs. Further efforts are needed in strain selection for cultivation in wastewater or inexpensive fertilizer. Common algal strains Nannochloropsis sp. and Chlorella sp. were studied to determine effects. Both strains were exposed to standard nutrients, which acted as controls, and high levels of NPK to simulate wastewater. The results revealed that NPK had a positive effect on turbidity and dissolved oxygen while decreasing the lipid productivities (measured via hexane solvent extraction) by an average of 36.5%. Specifically, Nannochloropsis sp. had overall higher values for all dependent variables. It is believed that under nutrient limiting conditions the cells deposited fatty acids in a triacylglycerol pathway. A follow-up experiment was performed using salinity as a novel method of decreasing biomass while maintaining lipid viability. Results revealed that freshwater algae can be cultivated in salinity levels between 10-15 ppt in order to increase lipid production. It is believed that while salinity osmotically interfered with the cell, lipid content increased, acting as a protective mechanism. Future research should focus on optimizing lipid production under stressed conditions using genetic manipulation of the TAG biosynthesis pathway.
Keywords: Biofuel; Lipids; Algae; Chlorella; Nannochloropsis; Salinity Stress; Biomass; Nitrogen and Phosphorus and Potassium; Novel; Optimization